WANT TO CONNECT WITH NATURE, LET’S CLIMB - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
Exploring the beauty of the forest from the treetops is an activity that you should not miss. According to the Founder of Tree Climbing Planet, Tim Kovar who has 25 years of experience in tree-climbing, this activity is the best way for us to connect with nature. Tim, who is also a Certified Master Tree Climbing Instructor added that, by getting involved in this thrilling activity, you will discover magnificent aspects of nature waiting to be discovered.